THE URGENCY OF CHILDREN'S CHARACTER FORMATION FROM PERSPECTIVE IMAM GHAZALI - Abdullah, Burhan; Nurul Hidayati Murtafiah (Cakrawala Pedagogik, 2023)
The process of forming a quality character needs to be formed early on and must be as maximal as possible. However, character education alone is not enough to build good character. Character education methods are needed that not only develop aspects of moral development but are also spiritually based, which were extracted from experts who were experts at the time, namely Imam Al-Ghazali. This research is library research, the data collection is done by means of data documentation. Meanwhile, the data was analyzed using an interpretation of the urgency of the context of child formation. The results of the research show that the urgency of character formation from Imam Al-Ghazali's perspective aims to make a noble soul, not just a mere process, nothing but a process that has a spirit, every activity is shown to the virtues consisting of moral values. The highest moral value is monotheism, namely the oneness of Allah Subhanahuwata'ala and noble character.